Testing the Conceptual Model of Creativity-based Teaching Method among High School Students - Hoseini, Mhammad Sadegh; Sohrabi, Nadereh; Baghooli, Hosein; Barzegar, Majid (Iranian evolutionary educational psychology journal, 2020)
Creativity is the desire for creativity that is potentially present in all people and at all ages and is directly and closely related to the socio-cultural environment. Teaching method refers to activities that are designed by the teacher with the aim of facilitating learning between the teacher and one or more learners in the form of interaction. The aim of the present study was testing the conceptual model of creativity-based teaching method among high school students. It was conducted on a sample of experts (including principals, deputies, teachers and counselors) working in 20 public schools in Shiraz (384 people, including 250 males and 134 females) in the academic year of 2019-2020. The method of the present study was a correlational in which researcher-made questionnaires were distributed among the subjects, and then, the fitness of the proposed model and the effect of teaching methods on creative learning were examined using AMOS 24 software. The results of statistical tests showed that students' creativity is influenced by teaching methods.